Delayed Soft Tissue Reconstruction with a Horizontal Rectus Abdominis Musculocutaneous Flap following Hip Exarticulation. (19th August 2013) - Rødgaard, Jes Christian; Tei, Troels Michael
Abstract : Coverage of large soft tissue defects at the hip region constitutes a challenge for plastic surgeons. We report the case of a 43-year-old female with necrotizing fasciitis of the right thigh, necessitating hip exarticulation and substantial debridement of necrotic tissue. An ipsilateral horizontal rectus abdominis myocutaneous (HRAM) flap was used to cover the defect. The reconstruction was carried out after the attempt of local tissue rearrangement. In light of the successful outcome, we propose that this flap be considered in the future planning of soft tissue reconstruction at the hip region.